Obituary: Professor Joseph Andy Soesilo - Founder of Jurnal Dimensi - predecessor of Civil Engineering Dimension journal - Djwantoro Hardjito; Benjamin Lumantarna (Institute of Research and Community Outreach - Petra Christian University, 2015)
Obituary: Professor Joseph Andy Soesilo Founder of Jurnal Dimensi - predecessor of Civil Engineering Dimension journal Djwantoro Hardjito & Benjamin Lumantarna | Civil Engineering Dimension May 25, 2015 Professor Joseph Andy Soesilo passed away on Friday, May 22, 2015 at the age of 71, in Tempe, Arizona, USA. Born in Blora, Central Java, Indonesia as Djwa Bian An, Andy came to Surabaya to pursue his tertiary education and received his bachelor’s degree in civil engineering from Petra Christian University in 1972. He was in the first batch of students in the civil engineering department in the university in 1962. He got his masters degree from the Asian Institute of Technology, Thailand, in 1976, and later on his Ph.D from the Department of Geography, Arizona State University, Tempe, USA in 1982. During his studentship, Andy was actively involed in student movement. Among others, he pioneered the student magazine GENTA in 1964, especially to promote the university to wider community. GENTA is still exist right now, and considered as one of the oldest student magazines in Indonesia. Andy was the first president of the student council in the university, in the era which was characterized with political turmoil in the country. He joined the Civil Engineering Department at Petra Christian University as lecturer in 1972, later becoming the Director of Student Affairs in the University from 1976-1977, and Director of Research and Community Outreach from 1977-1981. While at Petra Christian University (PCU), he made major contributions to the establishment of Jurnal Dimensi in 1980, a journal to publish scientific articles, particularly resulted from research carried out by PCU lecturers and scholars. This journal is the predecessor of the current Civil Engineering Dimension Journal and several other journals published by PCU. The establishment of Jurnal Dimensi was visionary and exemplary, as at that time publication of scientific articles has yet to become obligation to Indonesian lecturers. Until his last day, Andy has served as a member of the International Advisory Board of CED journal. In 1982, Andy moved to USA, to join the Arizona State University (ASU) as a Research Associate until 1988. For twenty years from 1988, Andy was affiliated with Arizona Department of Environmental Quality (ADEQ) as an environmental planner. Following his retirement from ADEQ, He was still lecturing as an adjunct professor at Urban Planning Department at ASU. Together with several friends, he founded Persekutuan Kasih Kristus Arizona (PKKA), Inc., a foundation to help Indonesian Christian schools in the rural areas. Among his publications are ‘Site Remediation: Planning and Management’ (CRC Press, 1997) and ‘Hazardous Waste Planning’ (CRC Press, 1995). He supposed to present his paper entitled ‘The Role of Municipal WWTPs in Arizona’s Water Conservation’ in the coming ‘The Fifth Euro Asia Civil Engineering Forum’ (EACEF-5) conference, to be held at Petra Christian University, Surabaya, Indonesia, from 15-18 September 2015. Andy, who had lived in Tempe, Arizona, USA, was the husband of Ursula (Lanny) Soesilo and the father of Irene and Stanley Soesilo.